Measuring What Matters: Achieving Consensus on a Positive Aging Indicator Set For Ireland. Issue 3 (27th May 2019) - Gibney, Sarah; Sexton, Eithne; Shannon, Sinead
ABSTRACT: The objective of this study was to measure consensus among expert stakeholders on a set of positive aging outcome indicators in Ireland. Stakeholders from academic, public, and voluntary sectors and older people participated in a 3-round, online Delphi study to evaluate indicators for participation, security, healthy aging, attitudes to aging, and information access. Evaluation criteria included: acceptability, utility, accessibility, ranking, and balance and coherence. Consensus was achieved on 56 key indicators that are aligned with action areas in the National Positive Ageing Strategy. These indicators will be reported on a biannual basis to monitor progress in positive aging in Ireland.